Cemeteries as cultural heritage: implementing the model of cemeteries-cultural heritage as education environment - Pliberšek, Lidija (Mednarodno inovativno poslovanje, 2019)
Nowadays we can notice significant changes and variations in dealing with death around Europe which requires adaptation of services that cemeteries provide in their vast space. Providing new services is a challenging management issue that first requires a change in the perception of cemetery away from burial space. Purpose of this paper is to analyse how cemeteries can be used as education environment.
Keywords: cemeteries; cultural heritage; izobraževalno okolje; kulturna dediščina; learning environment; percepcija; perception; pokopališča; school; šola